Paradoxe entre idéal démocratique et autocensure des personnes racisées en milieu de travail : l’expérience d’une clinique de l’interculturalité - Sophie Hamisultane (Communiquer)
In our contemporary societies where people are confronted by the requirements of performance and adaptability, and where, moreover, the democratic ideal persists, how people being the subject of racism in the workplace deal with such issues? What power of speech is giving to them and how is it being given? The organizations must show fairness toward their employees, thus supporting a democratic ideal where each worker would have the same rights and liberties. Nevertheless, relations of domination and oppression persist. Concurrently, in those organizations the subject confronts the implicit injunction to be efficient, to be autonomous and to be productive. The subject becomes responsible for his integration into the collective and he has to carry the responsibility to live “well” in the workplace. Our article will question the self-censorship of people being subjects of racism and who are not able to tell it at the risk of, seemingly being unproductive. Through a specific research methodology, we also reveal a clinic of interculturality as an approach of intercultural intervention.